Stress Management Strategies and Work Performance of Graduate Students in Tomas Claudio Colleges - Peñaranda, Paula Cristin Jade; Peñaranda, Concepcion; Manalo, Ruel; Dungca, Catherine; Fernando, Claire Donnah; Francisco, Ma. Danielli; De Rosas, Eva; Perez, Kristel Mary (International Journal of Sustainability and Advanced Integrated Research, 2026)
Graduate students face many stressors stemming from academic workload, balancing work and study responsibilities, time constraints, and emotional pressures. This study investigated the relationship between stress management strategies and the work performance of graduate students during the Academic Year 2025–2026 using a descriptive-correlational research design. Data collected from 202 graduate students of Tomas Claudio Colleges through a structured questionnaire revealed that students often employed stress management strategies, with time management and cognitive-emotional regulation being the most frequently used. Social support and physical-recreational activities were also practiced, though to a slightly lesser extent. Work performance was rated very satisfactory overall, with students demonstrating high productivity, commitment, and quality of work. Correlational analysis indicated a significant positive relationship between stress management strategies and work performance, with time management showing the strongest association. These findings suggest that effective coping strategies enable students to maintain both academic and professional responsibilities successfully.
Keywords: Graduate students, Stress management strategies, Time management, Cognitive-Emotional regulation, Work performance, Social support